Strategies for Enhancing Graduate Employability in Islamic and State Universities: A Comparative Study in Indonesia - Adriansyah, Muhammad Ali; Handoyo, Seger; Margono, Hendro; Tondang, Edoardo; Julian, Antoni (Madania: Jurnal Kajian Keislaman, 2025)
This study explores strategies to enhance graduate employability in Indonesia’s Islamic-based universities and state universities. Employing a descriptive qualitative approach, data were collected through in-depth interviews with university managers, lecturers, students, and alumni, supported by documentation studies and participatory observations. Thematic coding and data triangulation were used to analyze the data, ensuring the depth and validity of findings. The results reveal distinct institutional approaches: Islamic universities emphasize character development and work ethics rooted in spiritual values through programs like tahfiz-based leadership training and religious mentoring, while state universities focus on strengthening technical competencies and industry networks through structured internships and career development centers. Despite these differences, both institutions actively align higher education with labor market needs. This research contributes to the theoretical discourse on employability by introducing a new conceptual framework that integrates spiritual values with professional skills. The framework includes three core components: values-based curriculum integration, collaborative industry engagement, and holistic graduate profiling. These findings offer insights for policymakers and educators in developing inclusive and contextually relevant higher education models in pluralistic societies. Penelitian ini mengkaji strategi peningkatan daya saing lulusan di perguruan tinggi berbasis Islam dan perguruan tinggi negeri di Indonesia. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara mendalam dengan pimpinan universitas, dosen, mahasiswa, dan alumni, serta didukung oleh studi dokumentasi dan observasi partisipatif. Analisis data dilakukan melalui teknik pengkodean tematik dan triangulasi untuk menjamin kedalaman dan validitas temuan. Hasil penelitian menunjukkan adanya pendekatan kelembagaan yang berbeda: perguruan tinggi Islam menekankan pada pembentukan karakter dan etos kerja yang berlandaskan nilai-nilai spiritual melalui program seperti pelatihan kepemimpinan berbasis tahfiz dan pembinaan keagamaan, sedangkan perguruan tinggi negeri lebih menitikberatkan pada penguatan kompetensi teknis dan jaringan profesional melalui program magang terstruktur dan pusat pengembangan karier. Meskipun memiliki perbedaan karakteristik, kedua jenis institusi sama-sama menunjukkan upaya aktif dalam menghubungkan pendidikan tinggi dengan kebutuhan dunia kerja. Secara akademik, penelitian ini berkontribusi dalam pengembangan diskursus teoretis mengenai employability dengan menawarkan kerangka konseptual baru yang mengintegrasikan nilai-nilai spiritual dengan keterampilan profesional. Kerangka ini mencakup tiga komponen utama: integrasi kurikulum berbasis nilai, kolaborasi strategis dengan dunia industri, dan profil lulusan yang holistik. Temuan ini memberikan wawasan bagi para pengambil kebijakan dan pendidik dalam merancang model pendidikan tinggi yang inklusif dan kontekstual di masyarakat yang pluralistik.